Integration of sorption enhanced reforming with biomass gasification for highly purified hydrogen production - Atas, Ali; Javani, Nader; Yucel, Ozgun (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Biomass gasification integrated with Sorption-Enhanced Reforming (SER) provides an advanced thermochemical pathway for high-purity hydrogen production while minimizing carbon emissions. In this study, a fixed-bed gasification model is developed and validated using Aspen Plus (R) for three organic waste-based feedstock: municipal solid waste (MSW), poultry waste (PW), and food waste (FW). The integration of SER employs calcium oxide (CaO) as a solid sorbent to capture CO2 in situ, shifting the chemical equilibrium toward hydrogen formation via water-gas shift and reforming reactions. The simulation results indicate that hydrogen purity reaches up to 99.4 % at 923 K and 20 bar. Among the tested feedstocks, food waste yielded the highest Hydrogen mole fraction at 94 %, followed by PW (92.8 %) and MSW (92.2 %). Additionally, CO2 capture efficiency exceeded 90 %, demonstrating the system's capability to operate near carbon neutrality. Sensitivity analyses highlight the critical impact of gasifier temperature, equivalence ratio, and air mass flow rate on syngas quality and hydrogen yield. The hybrid process not only intensifies hydrogen generation but also integrates carbon capture without additional downstream units. This work presents a scalable, efficient, and environmentally sustainable approach for hydrogen production from diverse organic waste streams, supporting the development of low-emission energy systems for future industrial deployment.
Keywords: Biomass gasification; Sorption enhanced reforming; Aspen Plus; Hydrogen; Carbon capture and storage; LOOPING PROCESS CLP; STEAM GASIFICATION; FLUIDIZED-BED; PERFORMANCE ANALYSIS; COAL-GASIFICATION; SYNGAS PRODUCTION; H-2 PRODUCTION; CO2 CAPTURE; SIMULATION; GASIFIER; Chemistry; Electrochemistry; Energy & Fuels